Prínos enteroklýzy pro diagnostiku nádorů coecum-colon ascendens - Chmel, J; Horejsí, A; Kodadová, J (Casopis lekaru ceskych, 1998)
In two patients examination of the small intestine by enteroclysis was indicated on account of haemorrhage into the digestive tract and severe anaemia and in one patient the ultrasonographic picture arousing suspicion of Crohn's disease of the terminal ileum. Although in all instances previously colonoscopy was made, considered complete, in one instance also irrigoscopy, with a negative result, enteroclysis revealed and surgery confirmed extensive carcinomas of the caecum and colon ascendens. The authors discuss the value and problems of the applied diagnostic method.
Keywords: Contrast Media; kontrastní látky; Colonic Neoplasms; Female; nádory slepého střeva; Humans; ženské pohlaví; Radiography; lidé; nádory tračníku; lidé středního věku; Middle Aged; Cecal Neoplasms; radiografie